Inclusive Growth – Institutions Matter! - Michael Grömling; Hans-Peter Klös (Intereconomics, 2019)
The aim of the concept of inclusive growth is to derive political recommendations on the basis of selected indicators so that a maximum number of socio-economic groups may benefit from the economic progress of a country. On the one hand, this initiative continues the long-running debate on alternative welfare measures beyond GDP-per-capita. On the other, the discussion on the relationship between growth and distribution is being revitalised. This article deals with the potentials and limitations of the concept of inclusive growth. Conventional inclusive growth concepts are less embedded within a growth context and not focused on political frameable institutions. The indicators focus on results or outcome rather than on growth drivers. In addition, outcome variables are mixed with supply-side indicators. Therefore, the conventional concepts should be further developed into an institution-oriented 'inclusive growth accounting' with a focus on the growth factors of labour, education and capital.
Keywords: 330